Adding dimension to cellular mechanotransduction: Advances in biomedical engineering of multiaxial cell-stretch systems and their application to cardiovascular biomechanics and mechano-signaling. (November 2017) - Friedrich, O.; Schneidereit, D.; Nikolaev, Y.A.; Nikolova-Krstevski, V.; Schürmann, S.; Wirth-Hücking, A.; Merten, A.L.; Fatkin, D.; Martinac, B.
Abstract: Hollow organs (e.g. heart) experience pressure-induced mechanical wall stress sensed by molecular mechano-biosensors, including mechanosensitive ion channels, to translate into intracellular signaling. For direct mechanistic studies, stretch devices to apply defined extensions to cells adhered to elastomeric membranes have stimulated mechanotransduction research. However, most engineered systems only exploit unilateral cellular stretch. In addition, it is often taken for granted that stretch applied by hardware translates 1:1 to the cell membrane. However, the latter crucially depends on the tightness of the cell-substrate junction by focal adhesion complexes and is often not calibrated for. In the heart, (increased) hemodynamic volume/pressure load is associated with (increased) multiaxial wall tension, stretching individual cardiomyocytes in multiple directions. To adequately study cellular models of chronic organ distension on a cellular level, biomedical engineering faces challenges to implement multiaxial cell stretch systems that allow observing cell reactions to stretch during live-cell imaging, and to calibrate for hardware-to-cell membrane stretch translation. Here, we review mechanotransduction, cell stretch technologies from uni-to multiaxial designs in cardio-vascular research, and the importance of the stretch substrate-cell membrane junction. We also present new results using our IsoStretcher to demonstrate mechanosensitivity of Piezo1 in HEK293 cells and stretch-induced Ca 2+ entry in 3D-hydrogel-embedded cardiomyocytes.